Pemanfaatan Energi Baru Terbarukan Smart Farming System dalam Peningkatan Hasil Pertanian dan Perikanan - Restiadi Bayu Taruno; Ilham Unggara; Joang Ipmawati; Yana Hendriana; Nur Azmi Ainul Bashir; Zulkhairi Zulkhairi (Universitas Muhammadiyah Yogyakarta, 2023)
Pondok Pesantren (Ponpes) Lintang Songo is a business-based boarding school with 27 business units. Those business units include agriculture, plantations, fisheries, and animal husbandry. Alas, the most common problems in business management are irregular fish feeding, unchecked water quality leading to many fish growing slowly or dying, and the high use of PLN electricity for business unit operations. The aim of the Community Service Program (PKM) was to design automatic tools supported by New Renewable Energy (EBT) technology based on the Internet of Things (IoT) in the form of a Solar Home System. Automatic feeding devices and pond water quality sensors were targeted to overcome the aforementioned issues. The method used in the Community Partnership Program (PKM) was research and development (RD) through the design of the Solar Home System, automatic feeding devices, and pond water quality sensors. After testing the fish feed tools, the condition of the fish improved, and no fish died. Monitoring the pH of pond water shows a pH value of 6.5 – 7 so that it can be categorized as normal with a stable water circulation system. Testing of the solar home system showed the effectiveness of using solar panels at position 120 WP in sunny conditions, which indicates that the utilization of supporting equipment for smart farming at the Lintang Songo Islamic Boarding School had been successful.